Biochemical impact of ALAEm supplementation in late gestation on the reproductive performance of sows - Zhao, Linlu; Zhang, Jin; He, Jieyi; Ma, Xingbin; Yu, Zhichao; Yong, Yanhong; Li, Youquan; Ju, Xianghong; Liu, Xiaoxi (Frontiers in Veterinary Science, 2025)
Adding plant extracts to diets to enhance sow performance and health is widely regarded as a healthy and sustainable practice. In promoting antibiotic-free farming, plant extracts have emerged as a leading solution for enhancing sow fertility through nutritional strategies. The aim of this study was to investigate the biochemical impacts of supplementation of sows with ALAEm (composed of nine plant extracts) on blood and placental indices of sows in late gestation. The components of ALAEm were determined by UPLC-MS/MS. 196 normal gestation parturient sows were randomly allocated into two groups (n = 98 per group): the control group and the test group fed 20 g/d ALAEm supplementation at 74–114 d of gestation. The study examined the various clinical indexes in the blood, the expression of genes and proteins and metabolomics in the placenta. Dietary ALAEm supplementation improved sow reproductive performance (total number of piglets born alive, number of piglets weaned, wean weight), serum biochemical indices, placental structure and increased gene and protein expression of ZO-1, Claudin-1 and other placental junction-associated factors. ALAEm attenuated placental tissue oxidation, inflammation, and apoptosis, promoted placental growth (EGF and IGF-1) and angiogenesis factors (VEGFA, PIGF and other factors), and increased the nutrient transport in placental (GLUT1 and SNAT2). Dietary ALAEm supplementation decreased the number of metabolites associated with lipid metabolism through alpha-linolenic acid metabolism. Therefore, dietary supplementation of ALAEm in the late gestation may improve fertility by reducing the levels of inflammation, oxidation and apoptosis in placental tissues via the EGFR/VEGFR2-PI3K-AKT1 pathway, promoting placental growth, angiogenesis and nutrient transport, and altering the levels of placental lipid metabolites via α-linolenic acid metabolism.